Проблемы безработицы как следствие политики в сфере занятости на рынке труда: Пример Словацкой Республики и Чешской Республики - ЖофчиноваВ.; ГрабовскаяЗ. (Вопросы государственного и муниципального управления, 2019)
A qualitative positive shift in regional development largely depends on human resources that create value and transform other development factors. A significant part of the emerging regional disparities in individual national economies also causes disparities in regional development at the achieved level of employment and unemployment. One of the significant quantifiable negative impacts on the level of regional development is the decline in gross domestic product as a key indicator of the economic progress of the country. The unimportant impact of the growth of unemployment is the decrease in economic growth both in the short and long term. Due to the fact that one of the goals of public administration organisations is to ensure the continuous positive economic and social development of the administered territory, the problem of identifying the dominant development trends in the labor market from the legislative and economic point of view can be considered highly topical. The main focus of the study is to analyze selected economic and legislative aspects of unemployment through the selected instruments of employment policy in the labor market and in the context of changes in gross domestic product. We used quantitative data characterizing the labor market and the economic development of the regions as well as the valid legislative norms as part of the desk- based analysis. To prove the dependence of the unemployment rate on real growth and vice versa, we used the theory of Okun´s law. Applying Eurostat data, we analyzed labour markets in the Czech and Slovak Republic. The labour market situation is examined in the context of the development of selected labor market indicators from 28-member states of the EU, collected from 2007–2016. The calculated regression model shows that the Czech Republic unemployment rate is more dependent on variation in real GDP growth rate than the Slovak one. The authors are worried that on the other hand, the trend of increasing the number of people of productive age plus the extension of the retirement age can act as a problem in terms of long-term unemployment and the imbalance on the labour market. The question of regularly increasing retirement (and its possible cessation) is a current problem in the Slovak Republic and also in the Czech Republic. And in this context, it could be also said that the current employment policy implemented in both countries does not satisfactorily reflects the merits of addressing the issues of unemployment.